Infestasi ektoparasit pada kambing korban bencana erupsi Gunung Semeru - Permata, Fajar Shodiq; Rossa, Sankha (School of Veterinary Medicine and Biomedical Sciences, Bogor Agricultural University, 2023)
The slopes of the volcano have soil fertility and environmental conditions suitable for businesses in the livestock and agricultural sectors. Raising livestock at the foot of an active volcano requires disaster mitigation against the risk of health problems and even death, which can be accomplished through a health examination. This research aims to identify ectoparasite infestations in goats victims of the Mount Semeru eruption disaster. Ectoparasite examination of each symptomatic goat in Kamarkajang Hamlet, Sumberwuluh Village, Lumajang Regency, East Java in March 2022 after the eruption of Mt. Semeru was carried out by taking samples directly from the lice and the eggs. Identification of ectoparasites using light microscopy. The identification results showed that Linognathus sp. and Bovicola sp. infested goats. There were 130 goats from 14 different cages; 6 goats (4.6%) in one cage were infested with lice, and 1 goat (0.8%) in another cage was suspected of scabiosis.